Manajemen Bimbingan dan Konseling Pada Masa Pandemi Covid-19 - Neni Khoerunnisa; Abdul Kosim; Kasja Eki Waluyo (Peneliti.net, 2022)
The existence of the COVID-19 pandemic has forced the government to make policies for student learning activities directed at online learning or online at home, but still with the supervision and control of teachers/counselors and parents through online learning. Guidance and counseling are efforts made to help optimize individuals. The individuals who are assisted are people of various ages, both men and women, individuals and groups and individuals in this case are individuals who are developing. In an educational institution, guidance and counseling is a very important component to promote the quality of schools. The method used is a qualitative method where this qualitative research method is considered the most appropriate because it can provide an overview of the reality regarding the management of guidance and counseling during the COVID-19 pandemic. The method used in data collection is using the interview method through the zoom application.